Hunting for fear: innovating management of human–wildlife conflicts. Issue 3 (26th March 2013) - Cromsigt, Joris P.G.M.; Kuijper, Dries P.J.; Adam, Marius; Beschta, Robert L.; Churski, Marcin; Eycott, Amy; Kerley, Graham I.H.; Mysterud, Atle; Schmidt, Krzysztof; West, Kate; Frair, Jacqueline
Summary There is a growing theoretical basis for the role of predation risk as a driver of trophic interactions, conceptualized as the 'ecology of fear'. However, current ungulate management ignores the role of nonlethal risk effects of predation. We introduce the concept of 'hunting for fear' as an extension of the more classical 'hunting to kill' that is typically used in large herbivore management. Hunting for fear aims to induce a behavioural response in ungulates, for example, as a way of diverting them from areas where their impact is undesired. Synthesis and applications. Hunting for fear asks for novel, potentially controversial, ways of hunting to induce strong enough risk effects, including more hunting on foot and with dogs, extended hunting seasons (ideally year‐round) and increased hunting of calves. Hunting for fear may offer novel opportunities to help manage the growing human–wildlife conflicts that we experience globally.